2000
DOI: 10.1128/aem.66.2.638-642.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Disulfide Isomerase Gene Fusion Expression System That Increases the Extracellular Productivity of Bacillus brevis

Abstract: We have developed a versatile Bacillus brevis expression and secretion system based on the use of fungal protein disulfide isomerase (PDI) as a gene fusion partner. Fusion with PDI increased the extracellular production of heterologous proteins (light chain of immunoglobulin G, 8-fold; geranylgeranyl pyrophosphate synthase, 12-fold). Linkage to PDI prevented the aggregation of the secreted proteins, resulting in high-level accumulation of fusion proteins in soluble and biologically active forms. We also show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The E. coli-B. choshinensis expression-secretion shuttle vector pNCMO2 was constructed by inserting the pUC119-derived ColE1 replication origin and ampicillin resistance gene (TaKaRa Shuzo) into pNH301 [20]. Additionally, the lac operator derived from pUC119 was inserted in front of a promoter 2 region, as described elsewhere [17].…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…The E. coli-B. choshinensis expression-secretion shuttle vector pNCMO2 was constructed by inserting the pUC119-derived ColE1 replication origin and ampicillin resistance gene (TaKaRa Shuzo) into pNH301 [20]. Additionally, the lac operator derived from pUC119 was inserted in front of a promoter 2 region, as described elsewhere [17].…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…There have been numerous reports on the development and application of fusion tags (Kang et al 2007), (Huang et al 2008),(Kajino et al 2000), (Sievi et al 2003) , (Ahn et al 2004), (Andres et al 2005). In this regard, we developed a novel fusion partner by using the S. cerevisiae ER membrane protein, Voa1p.…”
Section: Discussionmentioning
confidence: 99%
“…Another way to increase protein secretion is by direct fusion of the target protein to well-secreted proteins such as human serum albumin (Kang et al 2007), (Huang et al 2008) protein disulfide isomerase (Kajino et al 2000), Hsp150 protein (Sievi et al 2003) , cellulose-binding domain (Ahn et al 2004) and cell wall protein Pir4 (Andres et al 2005). The secretion-enhancing effects of such fusions are often attributed to the improved stability and transport of target proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, the bacterial foldases are not always capable to correctly fold the foreign protein, especially when several disulphide bridges are involved (Bolhuis et al, 1999b). When using a fungal protein disulphide isomerase (PDI) as fusion partner to secrete heterologous proteins in B. brevis, Kajino et al (2000) observed an 8-fold and 12-fold increase of extracellular production of light chain of immunoglobulin G and geranylgeranyl pyrophosphate synthase, respectively. Linkage to PDI prevented aggregation of the proteins resulting in high-level accumulation of the fusion proteins in soluble and biologically active forms.…”
Section: Protein Foldingmentioning
confidence: 99%